Nourish : simple recipes to empower your body and feed your soul - Bündchen, Gisele, 1980-; Hutton, Elinor (Clarkson Potter, 2024)
"World-renowned model and wellness advocate Gisele Bundchen presents a collection of 100 delicious, accessible recipes focused on kickstarting and maintaining a healthy lifestyle while finding balance and intention through food. Superstar model and environmental activist Gisele Bundchen believes wellness begins with food. At home, she follows an 80/20 plan, with 80% of her diet focused on fueling her body with healthy and lean proteins and nutrient-rich vegetables while the remaining 20% is reserved for eating with more flexibility (hello mom's chicken lasagna!). In her first cookbook, she devotes the first quarter of the book to walking readers through adjusting to this new mindset and offers practical guidance for making it work. From breaking cycles to setting intentions, the merits of an occasional juice fast, buying in bulk, minimizing waste, and meal planning, this book of 100 recipes is as much about cooking as it is about living with mindfulness. Just like many of us, Gisele is no stranger to restrictive diet fads and unhealthy eating habits. In Nourish, she provides guidance on how to create a routine filled with positive intention, delicious food, and gratitude to improve your health and mindset"--